CONSTRUCTING MOODLE-BASED ONLINE LEARNING FOR VOCATIONAL SCHOOL - Arwidiyarti, Dwinita; Hikmi, Henni Comala (Jurnal Pilar Nusa Mandiri, 2020)
During the Covid-19 pandemic, every level of educational institutions is demanded to employ online learning based on their condition and capability. Many efforts have been done to sustain the teaching and learning process without a face-to-face system. The characteristic of the learning model in vocational school is identical to education specified in the technical field which encompasses several fields of expertise and is passed down to expertise program and expertise competency which require an integrated system. One of the ways to meet the demand is constructing online learning with a learning management system based on Moodle (Modulator Object-Oriented Dynamic Learning Environment). The aim of this model is to create an effective and integrated learning environment in order to create ease in observation and evaluation. This research used Zachman Framework which was started by determining scope system encompassing data, process and computer network configuration; designing business model by using Use Case Diagram; designing the model of the information system by using Class Diagram, Activity Diagram and Sequences Diagram; designing technology model by creating users’ interface program; and proceed to the implementation by customizing the Moodle software to create Moodle-based online learning which can be used in vocational schools.